Sweetbrew Coffee / Sarah Qistina Saiful Muzamir ... [et al.] - Saiful Muzamir, Sarah Qistina; Herman, Siti Humaira; Noor Azmee, Sara Nur Imani; Junaidey, Sarah Najwa (2021)
SweetBrew café is a type of restaurant which, in addition to light refreshments such as baked goods or snacks, mainly serves coffee and tea. The word "café" comes from the French word "coffee" definition. The relaxed and welcoming feel is one of the key reasons why coffee shops have become so popular in recent times. The coffee shop offers a wonderfully calm atmosphere where people can meet friends to catch up on coffee, have a casual family lunch or concentrate on working in a relaxed atmosphere. It is a food and beverage service business and the target customers are teenagers, workers and families.